The Relationship Between Nurse Managers\' Leadership Styles and Procrastination in Nursing Staff in Isfahan Social Welfare Hospitals - Behrooz Rezaei; Mohammad Hossein Yarmohammadian; Hossein Mahmoodzadeh Ardakani (مراقبت پرستاری و مامایی ابن سینا, 2017)
Introduction: Nursing leadership style is effective in the successful and timely performance of nursing care. Besides, nurses' procrastination will have high casualties and financial costs. This study aimed to determine the relationship between staff procrastination and nurse managers' leadership styles. Methods: This was a descriptive correlational study conducted at social welfare hospitals in 2013. The study population consisted of employees (n = 950) and managers (n = 70) of nursing and midwifery departments. All the managers and 290 employees were randomly selected by stratified method. Data were collected by demographic, organizational procrastination and Bardenz-Metzkas leadership style (LBDQ) questionnaires, of which the validity and reliability had been confirmed. Data were analyzed with correlation coefficient at 0.05 significance level. Results: Most of the managers had average task-oriented and people-oriented leadership styles, but the focus of the executers on task-oriented leadership style was greater. The staff had low procrastination (52.46 ± 12.99). People-oriented style of the managers had weak inverse correlation with procrastination scale (r = -0.176) and inefficiency subscale (r = -0.191) of the nursing staff; also, task-oriented leadership style had a weak inverse correlation with subscale of abomination from task performance (r = -0.110) in staff, but the relationships was not significant. Conclusions: Lack of procrastination in nursing and midwifery staff is a positive phenomenon that affects the performance of the organization. Due to the lack of relationship between leadership style and procrastination, future researches in larger extent is proposed.